2017
DOI: 10.21873/anticanres.11408
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Enhances TGFβ-mediated Epithelial-to-Mesenchymal Transition in Human Mammary Epithelial MCF-10A Cells

Abstract: Abstract. Aim: This study investigated the effect of reactive oxygen species (ROS) on transforming growth factor (TGF)-β-mediated epithelial-to-mesenchymal transition (EMT) inEpithelial-to-mesenchymal transition (EMT) is involved in many biological processes, including embryogenesis, tissue fibrosis and cancer metastasis. EMT is characterized by loss of cell polarity and adhesion, resulting in changes in cell morphology and increased cell migration and size (1, 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Similarly, extracellular signal-regulated kinase (ERK) inhibition could repress TGFβ and H 2 O 2 -induced EMT, further supporting the important role of ROS in TGFβ-induced EMT via the receptor tyrosine kinase pathways [120]. In accordance, another recent finding indicated H 2 O 2 -enhanced TGFβmediated EMT via SMAD and MAPK kinase (MEK)/ERK signaling in MCF-10A human mammary epithelial cells [126] (Fig. 4).…”
Section: Redox Regulation Of Tgfβ-mediated Emtsupporting
confidence: 74%
“…Similarly, extracellular signal-regulated kinase (ERK) inhibition could repress TGFβ and H 2 O 2 -induced EMT, further supporting the important role of ROS in TGFβ-induced EMT via the receptor tyrosine kinase pathways [120]. In accordance, another recent finding indicated H 2 O 2 -enhanced TGFβmediated EMT via SMAD and MAPK kinase (MEK)/ERK signaling in MCF-10A human mammary epithelial cells [126] (Fig. 4).…”
Section: Redox Regulation Of Tgfβ-mediated Emtsupporting
confidence: 74%
“…Roles of interstitial collagen and BM collagen in mammary tumor development have been determined [ 61 – 63 ]. However, function of membrane-associated collagens in breast cancer is not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that increased Cdh2 expression confers further migrative abilities to PCa cells and thereby increases their metastatic potential (28). Since it has been shown that oxidative stress alters E-and N-cadherin levels in pancreas and breast cancers in previous reports (20)(21)(22), we investigated the effects of the sublethal dose of H 2 O 2 , which was determined in the previous step, on E-and N-cadherin levels in PCa cells. Indeed, we have observed that H 2 O 2 induced alterations in E-and N-cadherin levels are ERK dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Since the previous studies have reported that oxidative stress may cause a decrease in E-cadherin level and an increase in Ncadherin level in pancreas and breast cancers (20)(21)(22), the effects of a sublethal dose of H 2 O 2 on E-and N-cadherin protein levels were investigated in PCa cells. PC-3 and LNCaP cells were seeded on 60 mm plates and were treated with H 2 O or a 50 μM concentration of H 2 O 2 for 24 h. Total cell lysates were extracted and were used for western blotting.…”
Section: H 2 O 2 Treatment Alters E-and N-cadherin Levels In Pca Cellsmentioning
confidence: 99%
See 1 more Smart Citation